EFFECTS OF VISCOUS DISSIPATION ON MHD NATURAL CONVECTION FLOW OVER A SPHERE WITH TEMPERATURE DEPENDENT THERMAL CONDUCTIVITY IN PRESENCE OF HEAT GENERATION - Haque, Md. Raihanul; Alam, Md. M.; Ali, M. M.; Sheikh, M.A. Naim (European Scientific Journal, ESJ, 2014)
The objective of this research is to investigate the combined effects of heat generation and viscous dissipation on MHD natural convection flow of an electrically conducting fluid over an isothermal sphere with variable thermal conductivity. Thermal conductivity is considered as a linear function of temperature. The governing equations are solved numerically by numerical solution strategy as per requirement and suitability. Solution method such as finite difference method with killer box scheme has been employed. The computational findings for the dimensionless velocity, temperature profiles as well as for the skin-friction coefficient and surface heat transfer rate are displayed graphically.